Diatom abundance in Lake Aoki sediment as a proxy in demarcating the timing of the last Glacial-Holocene transition in central Japan (Journal of Nepal Geological Society, 2011)
A 15 m long sediment core from Lake Aoki, central Japan was investigated for its diatom abundance to determine if the abundance change with time provides a reasonable basis to reconstruct the timing of the last Glacial-Holocene climate shift in central Japan. Silty clay dominated the sediment lithology, and the tephra and radiocarbon based age determinations provided an excellent sediment chronology extending back to the beginning of the lacustrine sedimentation ca. 43ka cal BP. The diatom abundance in the sediment showed a marked change at 13 ka cal BP, with a mean concentration of ca. 1.8x105 frustules mg-1 dry sediment before and ca. 10.3 x 105 frustules mg-1 dry sediment after that time. This abrupt increase in abundance after 13 ka cal BP is attributed to the increase in diatom productivity in the lake due to the climate shift from the last Glacial cold to the Holocene warm condition. The timing of rapid diatom abundance rise, 13 ka cal BP, in Lake Aoki sediment record appears to be the last Glacial-Holocene transition in central Japan.